Unusual location of lichen striatus in an adult patient - Temiz, Selami Aykut; Ataseven, Arzu; Dursun, Recep; Özer, İlkay and Oltulu, Pembe (The European Research Journal, 2019)
Lichen striatus is a rare inflammatory dermatosis that influences mostly children, being rare reports in adults. The pathogenesis is unknown. In addition, lichen striatus is demonstrated as T-cell mediated inflammatory cutaneous disease. It is characterized by linear tendency, usually on the extremities. Its most typical property is the linear arrangement of slightly raised, lichenoid papules. A 28-year-old woman presented with a 3-month history of an asymptomatic linear erythematous violaceous papular lesions on her left abdominal area. Skin biopsy was performed in terms of differential diagnosis from other linear distributions of inflammatory dermatoses. Histopathological examination revealed hyperkeratosis, acanthosis, focal parakeratosis, exocytosis, subbasal dissociation of an area, vacuolar degeneration of the basal membrane, perivascular and lichenoid lymphocytic infiltration. As a result, our case was diagnosed as lichen striatus, clinically and histologically. Topical pimecrolimus ointment twice a day therapy was preferred in the patient.